High residual carriage of vaccine-serotype Streptococcus pneumoniae after introduction of pneumococcal conjugate vaccine in Malawi - Todd D. Swarthout (Nature Portfolio, 2020)
Impact of pneumococcal conjugate vaccines (PCV) in controlling carriage needs to be evaluated to inform vaccine policy. Here, Swarthout et al. show in a prospective rolling cross-sectional study in Malawi a high residual prevalence of vaccine-serotype S. pneumoniae 7 years after PCV introduction.